Novel Adeno‐Associated Viral Vector Delivering the Utrophin Gene Regulator Jazz Counteracts Dystrophic Pathology in mdx Mice. Issue 9 (September 2014) - Strimpakos, Georgios; Corbi, Nicoletta; Pisani, Cinzia; Di Certo, Maria Grazia; Onori, Annalisa; Luvisetto, Siro; Severini, Cinzia; Gabanella, Francesca; Monaco, Lucia; Mattei, Elisabetta; Passananti, Claudio
Abstract Over‐expression of the dystrophin‐related gene utrophin represents a promising therapeutic strategy for Duchenne muscular dystrophy (DMD). The strategy is based on the ability of utrophin to functionally replace defective dystrophin. We developed the artificial zinc finger transcription factor "Jazz" that up‐regulates both the human and mouse utrophin promoter. We observed a significant recovery of muscle strength in dystrophic Jazz‐transgenic mdx mice. Here we demonstrate the efficacy of an experimental gene therapy based on the systemic delivery of Jazz gene in mdx mice by adeno‐associated virus (AAV). AAV serotype 8 was chosen on the basis of its high affinity for skeletal muscle. Muscle‐specific expression of the therapeutic Jazz gene was enhanced by adding the muscle α‐actin promoter to the AAV vector (mAAV). Injection of mAAV8‐Jazz viral preparations into mdx mice resulted in muscle‐specific Jazz expression coupled with up‐regulation of the utrophin gene. We show a significant recovery from the dystrophic phenotype in mAAV8‐Jazz‐treated mdx mice. Histological and physiological analysis revealed a reduction of fiber necrosis and inflammatory cell infiltration associated with functional recovery in muscle contractile force. The combination of ZF‐ATF technology with the AAV delivery can open a new avenue to obtain a therapeutic strategy for treatment of DMD. J. Cell. Physiol. 229: 1283–1291, 2014. © 2014 Wiley Periodicals, Inc.